Digital transformation in public sector governance: international experiences and lessons for Vietnam - Tai Le Khanh (Journal of State Management, 2025)
Applying comparative-analytical methods, this article synthesizes the digital transformation experiences of three countries: Ukraine, South Korea, and Singapore. The research findings show that countries that have achieved success implement digital transformation strategies in a comprehensive manner - from institutional frameworks and infrastructure to enhancing the digital capacity of citizens - in which the government plays the role of architect and leader throughout the entire process. On that basis, the article identifies lessons and requirements for Vietnam in implementing digital transformation, particularly emphasizing the need to enhance citizens’ digital capacity, build a unified data ecosystem, and develop technological infrastructure. The research results provide scientific evidence for policymaking and for developing digital transformation programs suitable for Vietnam’s conditions in the current period and in the years to come.